SISTEM KOMPENSASI NON-FINANSIAL BERBASIS NILAI SPIRITUAL DAN PENGARUHNYA TERHADAP RETENSI DAN MOTIVASI GURU HONORER DI LEMBAGA PENDIDIKAN NAUGAN PESANTREN - Arju Sarira Rahmawati (CV. ADIBA AISHA AMIRA, 2026)
This study aims to explore and qualitatively analyze the practices of non-financial compensation systems aligned with spiritual values within educational institutions under the auspices of the Islamic boarding school Darussalam Blokagung, Banyuwangi. This instrumental single case study is driven by the paradox of high loyalty among honorary teachers despite minimal financial compensation. The research focuses on elements of spiritual-based non-financial compensation, such as the recognition of barakah, opportunities for khidmat (devoted service), support for spiritual career development, and a sense of belonging to the pesantren community. Data collection was conducted through in-depth observation and interviews to achieve depth and data validity through triangulation. The results indicate that spiritual compensation significantly and positively influences the intrinsic work motivation and retention intentions of honorary teachers. This implementation transforms extrinsic motivation into strong intrinsic motivation and sincere devotion. In conclusion, spiritual compensation is a unique and effective human resource management strategy for addressing financial constraints in pesantren-based educational institutions, explaining the high teacher retention despite limited salaries.